PELATIHAN PENERJEMAHAN MAULID ADDIBA’I JAMAAH MASJID ATTAQWA TANDANG SEMARANG - Alif Al Hilal Ahmad; Suryo Ediyono; Muhammad Farkhan Mujahidin; Abdul Malik; Ahmad Jazuli (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Maulid nabi is one of the commemorations in Islam that aims to commemorate the birth of the Prophet Muhammad SAW. One of the activities that is often done in this commemoration is reading the book of maulid nabi which contains the history and life story of the Prophet Muhammad SAW. Masjid Attaqwa Tandang Semarang is a mosque that routinely organizes the Addiba'i maulid reading assembly which is held every Friday night after the isya' prayer in congregation. Most of the congregation who participated in the activity did not understand what was read. This activity aims to improve the congregation's understanding of the Addiba'i maulid text. The method used in this activity is meaning training and deepening material about maulid Addiba'i. From the evaluation results, it was found that the pre-test results showed 73% of participants had poor ability, 22% had sufficient ability, and 3% had good ability. After attending the training and taking the post-test, 17% of participants had sufficient ability and 83% had good ability.